Modern rehabilitation methods of cerebral palsy in children - L. B. Kuranova; B. I. Kherodinov (Лечащий Врач)
This is a review of rehabilitation options for children with cerebral palsy. The article provides a detailed analysis of the types, methods of treatment and rehabilitation, intended for rehabilitation therapists, general practitioners, and subject-matter specialists.